Transitions to democracy - Anderson, Lisa, 1950- (Columbia University Press, 1999)
Are the factors that initiate democratization the same as those that maintain a democracy already established? The scholarly and policy debates over this question have never been more urgent. In 1970, Dankwart A. Rustow's clairvoyant article "Transitions to Democracy: Toward a Dynamic Model" questioned the conflation of the primary causes and sustaining conditions of democracy and democratization. Now this collection of essays by distinguished scholars responds to and extends Rustow's classic work, Transitions to Democracy--which originated as a special issue of the journal Comparative Politics and contains three new articles written especially for this volume--represents much of the current state of the large and growing literature on democratization in American political science. The essays simultaneously illustrate the remarkable reach of Rustow's prescient article across the decades and reveal what the intervening years have taught us. In light of the enormous opportunities of the post-Cold War world for the promotion of democratic government in parts of the world once thought hopelessly lost of authoritarian and totalitarian regimes, this timely collection constitutes and important contribution to the debates and efforts to promote the more open, responsive, and accountable government we associate with democracy